"THE PEOPLE OF THIS COUNTRY HAVE HAD ENOUGH OF EXPERTS": IN DEFENSE OF THE "ELITES" OF THE SCIENCE‐AND‐RELIGION DEBATE: with Mark Harris, "'The People of This Country Have Had Enough of Experts': In Defense of the 'Elites' of the Science‐and‐Religion Debate"; Fern Elsdon‐Baker, "In Defense of Publics: Projection, Bias, and Cultural Narratives in Science and Religion Debates"; Elaine Howard Ecklund, Sharan Kaur Mehta, and Daniel Bolger, "A Way Forward for Sociological Research on Science and Religion: A Review and a Riff"; Nathan Crick, "Morality through Inquiry, Motive through Rhetoric: The Politics of Science and Religion in the Epoch of the Anthropocene"; and John H. Evans, "The Scope and Implications of Morals Not Knowledge.". Issue 3 (19th August 2019) - Harris, Mark
Abstract: This article takes a critical stance on John H. Evans's 2018 book, Morals Not Knowledge: Recasting the Contemporary U.S. Conflict between Religion and Science . Highlighting the significance of the book for the science‐and‐religion debate, particularly the book's emphasis on moral questions over knowledge claims revealed in social‐scientific studies of the American public, I also suggest that the distinction between the "elites" of the academic science‐and‐religion field and the religious "public" is insufficiently drawn. I argue that various nuances should be taken into account concerning the portrayal of "elites, " nuances which potentially change the way that "conflict" between science and religion is envisaged, as well as the function of the field. Similarly, I examine the ways in which the book construes science and religion as distinct knowledge systems, and I suggest that, from a theological perspective—relevant for much academic activity in science and religion—there is value in seeing science and religion in terms of a single knowledge system. This perspective may not address the public's interest in moral questions directly—important as they are—but nevertheless it fulfils the academic function of advancing the frontiers of human knowledge and self‐understanding.